BRI(BELT AND ROAD INITIATIVES ) AND ITS SOCIAL AND CULTURAL IMPACT ON PAKISTANI PEOPLE IN A QUALITATIVE APPROACH - Muhammad Fayyaz Khokhar; Professor Liu Bangfan; Tayyaba Zia (International Journal of Contemporary Issues in Social Sciences, 2024)
The BRI is an umbrella initiative spanning a multitude of projects designed to promote the flow of goods, investment, and people. The new connections fostered by the BRI could reconfigure relationships, reroute economic activity, and shift power within and between states. This study focuses upon The Belt and Road Initiative's role in the cultural and economic integration between China and Pakistan. Aims of the present study are to find the social, political and cultural factors that strengthen China’s connectivity with Pakistan and the world. It combines new and old projects, covers an expansive geographic scope, and includes efforts to strengthen hard infrastructure, soft infrastructure, and cultural ties. The study is purely based on a qualitative method, the sample of 20 respondents was selected and an in-depth interview method was used for data collection from Pakistan, on the topic of The Belt and Road Initiative's role in the cultural and economic integration between China and Pakistan. By the analysis of the data, researchers found the basic concepts and relationships about the BRI and culture or economic changes in Pakistan. So, this research concludes that the great BRI project is overall a positive step toward a bright future and it is going to rebuild the economy and infrastructure of Pakistan.